New Brazilian species of Endecous Saussure, 1878: Phallic sclerites, calling song and tegmen morphometry (Orthoptera: Grylloidea: Phalangopsinae) - Zefa, Edison [UNESP]; Mesa, Alejo [UNESP]; Martins, Luciano de P. [UNESP] (Wiley-Blackwell, 2010)
In this paper we describe the phalangopsid cricket Endecous alejomesai n. sp. collected from the cave "Lapa do Fuzil", Vila Propicio, State of Goias, Brazil. Diagnosis has been acquired by the combination of the following characteristics: phallic sclerite features; calling song with dominant frequency of 4.8 kHz and 52.9 +/- 5.8 (42-60, n = 22) cycles of sound per pulse; pars stridens with 90 +/- 6.84 (78-99, n = 12) teeth; mirror with one or two cross-veins; harp with two, three or four cross-veins.
Keywords: cave; cricket; Grylloidea; sonogram; taxonomy